Targeting the GFI1/1B—CoREST Complex in Acute Myeloid Leukemia - van Bergen, Maaike G. J. M.; van der Reijden, Bert A. (Frontiers in Oncology, 2019)
One of the hallmarks of acute myeloid leukemia (AML) is a block in cellular differentiation. Recent studies have shown that small molecules targeting Lysine Specific Demethylase 1A (KDM1A) may force the malignant cells to terminally differentiate. KDM1A is a core component of the chromatin binding CoREST complex. Together with histone deacetylases CoREST regulates gene expression by histone 3 demethylation and deacetylation. The transcription factors GFI1 and GFI1B (for growth factor independence) are major interaction partners of KDM1A and recruit the CoREST complex to chromatin in myeloid cells. Recent studies show that the small molecules that target KDM1A disrupt the GFI1/1B–CoREST interaction and that this is key to inducing terminal differentiation of leukemia cells.